Reinforced concrete structural design optimization: A critical review. (1st July 2020) - Afzal, Muhammad; Liu, Yuhan; Cheng, Jack C.P.; Gan, Vincent J.L.
Abstract: Building design optimization plays an important role in maximizing the reliability, cost efficiency, and environmental sustainability of constructed facilities. As the construction of reinforced concrete (RC) structures consumed tremendous amounts of steel reinforcement and concrete, RC structural design optimization for minimal environmental impact has attracted increasing attentions from academics and industry in recent years. Nowadays, new information technologies and computing techniques were increasingly utilized for the sustainable design and optimization of RC structures to maximize energy efficiency, but it still lacks a critical review to summarize the common research themes and highlight the future needs in this field. Therefore, the primary objective of this paper is to critically review the previous research related to the computational design optimization of RC structures for the minimum environmental impact, with the aim of highlighting the present status and future trends for the advancement of building design optimization. First, the general introduction and background for importance of multidisciplinary detailed design optimization of RC structures are described. Thereafter, a critical review of available research objectives, structural components, optimization strategies, and the use of different computational tools in RC structural design optimization to integrate sustainability in constructional design stage, is provided in this paper. Furthermore, different research trends are analyzed and critically discussed in detail. Potential research directions to better quantify and evaluate the implementation of detailed RC structural design optimization are presented. This paper can assist structural design practitioners in academia and industry to introduce new horizons of sustainable construction by considering multiple aspects of detailed RC structural design and combining several computational tools with optimization strategies. Graphical abstract: Systematic flow of suggested future researches in sustainable RC structural optimization. Image 1 Highlights: A holistic approach is proposed to support exhaustive review of the state-of-the-art research. The discussed research themes include cost, material, and environmental impacts. Only a few multidisciplinary aspects related to detailed design phase are conducted. Utilization of clash free and performance design strategies holds great future for design quality. Design for manufacturing & assembly can enhance the detailed design of steel reinforcement.